Healthy life expectancy: evaluation of global indicator of change in population health. - Robine, J M (1991)
OBJECTIVE--To review and evaluate the usefulness of healthy life expectancy as a global indicator of changes in a population's health. DESIGN--Review of all known studies to date from the United States, mainland Europe, Canada, and the United Kingdom that have used Sullivan's method of calculating disability free life expectancy. MAIN OUTCOME MEASURES--Life expectancy and disability free life expectancy. RESULTS--Over the past decade the average healthy life expectancy was 60 years for men and 64 for women, with the proportion of years of disability ranging from 11% to 21% in men and from 14% to 24% in women. At the age of 65 men could expect eight years of disability free life and women 10, with the life expectancy being respectively 14 and 19 years. The difference between the wealthiest and poorest income quintiles was 6.3 years in life expectancy and 14.3 in disability free life expectancy for men and 2.8 and 7.6 respectively for women. These results suggest that disparities in health are greater between social groups than between the sexes. Diseases affect mortality and morbidity differently. The order of importance for affecting life expectancy was circulatory disease, cancer, and accidents and for disability free life expectancy, circulatory disease, locomotor disorders, and respiratory disorders. CONCLUSIONS--Healthy life expectancy is a valuable index for the appreciation of changes in both the physical and the mental health states of the general population, for allocating resources, and for measuring the success of political programmes. Future calculations should also take into account the probability of recovery and thus extend the applicability of the indicator to populations in poor health rather than focusing on the well population.